Aligning Rural Tourism With Local Realities: Strategic Formulation Through AHP And TOWS In West Java - Abdurokhim; Guterres, Antonio (Journal of Tourism, Hospitality and Travel Management, 2023)
Rural tourism has emerged as a promising strategy for fostering inclusive and sustainable development in regions with rich natural and cultural assets. In Indonesia, particularly in West Java, the sector holds significant potential but remains constrained by infrastructure gaps, limited local capacity, and fragmented governance. This study aims to formulate strategic directions for rural tourism development by integrating the Analytical Hierarchy Process (AHP) and the TOWS Matrix. Through expert-based pairwise comparisons, four key criteria were prioritized: infrastructure, community participation, environmental sustainability, and governance support. Sub-criteria analysis revealed road connectivity and local leadership as top development levers. These priorities were then operationalized through a TOWS Matrix, generating strategy quadrants that matched internal strengths and weaknesses with external opportunities and threats. The resulting framework offers actionable strategies for rural tourism planning, emphasizing infrastructure investment, community empowerment, environmental regulation, and governance integration. The study contributes to the field by providing a replicable, evidence-based, and locally grounded decision-support model for sustainable tourism development in decentralized contexts.